Linguistic attribution of modern kazakh anthroponyms (Eurasian Journal of Philology Science and Education, 2020)
This article offers the stratigraphic analysis of modern Kazakh personal names. The data necessary to complete this study was collected from the birth records at the Departments of Civil Status Registration Offices (Almaly, Alatau, Auezov, Bostandyk, Zhetisu, Medeu, Nauryzbai, Turksib regions) of Almaty city. More than five thousand personal names of newborns born in2010 are subjected to this analysis. Modern Kazakh personal names are classified according to ethno-linguistic groups and subgroups. The ethnolinguistic aspect of the research allowed to reveal features of formation and development of modern Kazakh anthroponymy. The results of the study indicate that the Kazakh people were able to preserve the historical memory of culture and develop national traditions of naming through historical periods. The results of the research indicate that the national code of culture is preserved in Kazakh naming system as a fact of historical memory, the national traditions of naming are maintained accordingly. However, it should be noted that currently Kazakh anthroponymy is developing in four directions. Firstly, the Turkic-Kazakh traditions of naming are preserved, which are fundamental in the development of Kazakh anthroponymy. Secondly, there is an increase of Arabic names, which is associated with the growth of religious sentiment in society. Thirdly, penetration of Russian and European traditions of naming into Kazakh naming system. Fourthly, the occurrence of a new trend of naming: the formation of double names through a hyphen, double names that are written separately or together.